IJMA’ SEBAGAI PENYATUAN PERBEDAAN AWAL BULAN QAMARIAH - Ahmad Fadholi (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2020)
The teachings of Islam can be understood, because Islam brought by Prophet Muhammad pbuh. at 14 centuries ago, who was sent to convey Islamic teachings with the holy book, al-Qur’an as the principal teachings of Islam. While the second source is as-Sunnah. Both of them, al-Quran and as-Sunnah, are the principal source of Islamic teachings. Along with the times increasingly complex, the problems in people's lives are more and more undiscovered in these two sources. it is necessary for an ijtihad to finish its problems by way of ijma 'as a method of solving problems of religion. Ijma 'itself is an agreement of the mujtahid at some time after Prophet Muhammad on a syar'i law about a particular event. Events of the law faced by Muslims did’n stop by the death of the Prophet Muhammad pbuh. This problem, both in types and quality, is always developed according with evolution of time. Therefore, alternatives taken to determine the laws of any event are through ijtihad and make decisions together. That joint decision is called ijma ' and is the third argument agreed by sholars to be sources of law. Then by agreement as a third source of law, it have power in the Islamic legal system. The power of ijma' has been suggested by the Prophet in a hadith "La tajtami'u ummati' ala al-dhallah".